Applications of algae for environmental sustainability: Novel bioplastic formulation method from marine green alga - El Semary, Nermin; Alsuhail, Muneerah; Al Amer, Kawther; AlNaim, Abdulallah (Frontiers in Marine Science, 2022)
Background Chemical plastics cause global environmental pollution and can take hundreds of years to be naturally removed from the environment; therefore, eco-friendly alternatives are sought. In that regard, marine algae are considered a promising source for bioplastics. However, macroscopic algae from the Arabian Gulf, despite being produced in massive quantities every year, have never been exploited for this purpose. Moreover, most of the available studies have been primarily based on the extraction of specific components of algae to prepare algal bioplastics, which is laborious and costly and does not allow the use of all biological products of algae. Therefore, the present study aimed at generating biodegradable bioplastic from the whole biomass of a marine green macroscopic alga from the Arabian Gulf, Saudi Arabia, using a simplified method. Materials and methods The identity of this green alga was investigated using both morphological characteristics and molecular analysis. Different treatments from the literature were initially tried to yield a bioplastic blend, but did not work. The successful method included drying the green macroalgal biomass and grinding it until it becomes a fine powder, followed by sieving. The powder was placed in 100 ml water with other reagents and then autoclaved. The resulting mixture was further treated with glycerin. Several reagents were tested, but successful treatment was achieved with the combination of the ground seeds of Plantago ovata and the chemical plasticizer polyethylene glycol (PEG; Mw = 3,350). The algal biocomposite was effective in forming a tensile polymer whose properties were further enhanced by adding glycerin 1 day after making the blend. Spectrophotometric, thermal, and mechanical analyses of the blend were conducted, including Fourier transform infrared (FTIR) spectroscopy, dynamic mechanical analysis (DMA) for the mechanical properties, and thermogravimetric analysis (TGA) for thermal stability. The biodegradability of the blend was also examined in sandy soil for 3 months. Results The green alga was identified as macroscopic green alga Ulva sp., which was confirmed by both morphological and molecular analyses. The combination of a plant-based plasticizer and algal biomass formed a polymer with excellent tensile properties and thermal stability. FTIR confirmed the formation of a starch-based blend whose functional groups, O–H, C–H, C=O, and C–O, indicate the formation of a starch bioplastic derived from both starch and cellulose in the green alga and in P. ovata. Biodegradability was proven as the blend lost nearly 40% of its biomass after the soil burial test. Discussion Ulva sp. is a marine alga that is widespread in marine habitats. This particular alga is highly rich in carbohydrates including cellulose, hemicelluloses, starch, and ulvan, among other carbohydrates that constitute the major part of its dry weight. This alga and the plant plasticizer both contain starch as reserve food material. Both natural polysaccharides are excellent precursors for the formation of bioplastics and are completely biodegradable by soil microorganisms. PEG is also biodegradable by bacterial action. Therefore, the whole blend is not only biodegradable but also has suitable tensile strength and thermal stability. Conclusion The present study describes an eco-friendly novel method that is mostly based on using the whole algal biomass in addition to a natural plant material as a plasticizer, thereby providing a sustainable blend for the manufacturing of bioplastics for use in a number of applications, including agriculture, as it is biodegradable and can be utilized for composting and fertilizing plants.